Cobalt‐Carbon Core–Shell Nanoparticles Aligned on Wrinkle of N‐Doped Carbon Nanosheets with Pt‐Like Activity for Oxygen Reduction. Issue 21 (4th April 2016) - Li, Yuanyuan; Cheng, Fangyi; Zhang, Jianan; Chen, Zhimin; Xu, Qun; Guo, Shaojun
Abstract : A one‐step soft‐template induced strategy is demonstrated for the controlled synthesis of nitrogen‐enriched core–shell structured cobalt−carbon nanoparticles (NPs) sequentially aligned on wrinkles of N‐doped carbon nanosheets (Co‐C@NWCs). The key feature of Co‐C@NWCs for ORR catalysis enhancement is that it combines high catalytic centers of Co‐C core–shell NPs with the wrinkle of carbon nanosheets with high electron donation ability.